ChemInform Abstract: A Review (Part C) ‐ An Overview of Biological Activities of Schiff Base Transition Metal Complexes. Issue 12 (March 2015) - Anis, Itrat; Aslam, Muhammad; Afza, Nighat; Iqbal, Lubna; Noreen, Zahra; Hussain, Ajaz; Safder, M.
Abstract Review: [38 refs.